IMPROVING TRAINING OUTCOMES THROUGH BLENDED LEARNING - Reece, Michelle; Lockee, Barbara (Online Learning, 2005)
Blended learning is a prominent trend in corporate training that has implications for distributed learning across a range of venues and constituents. Typically defined as an instructional program offered through a combination of two or more delivery modes, blended learning utilizes a variety of approaches, including print-based materials, instructor-led training, and web-based training, to name a few. This article describes training strategies and techniques available through blended learning designs, such as pre-work, assessment strategies, and transfer activities. The authors outline the advantages and limitations of blended learning options and present a case study on how one organization, Certified Medical Representatives Institute (CMRI), made the shift to a blended approach in its course product line, highlighting both successes and challenges faced in the transition.